THE INFLUENCE OF PRICE, PRODUCT QUALITY, AND PROMOTION ON REPURCHASE INTEREST WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE ON MAYBELLINE PRODUCTS - Sri Dwi Ari Ambarwati; Adinda Nur Fauziah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to determine the effect of price, product quality, and promotion on repurchase intention, with consumer satisfaction as an intervening variable. This quantitative research uses a data collection tool in the form of a questionnaire. The population and sample in this study were 110 respondents, using primary data using the purposive sampling method. The criteria for respondents in this study were consumers who had bought and used Maybelline products at least twice. The data analysis technique used is path least squares (path analysis) with SmartPLS 3.0. The results of the study show that: 1) there is a partial and significant effect of price, product quality, and promotion on repurchase intention, 2) there is a partial and significant effect of price, product quality, and promotion on customer satisfaction, and 3) there is an effect of price, product quality, and promotion of repurchase intentions through partial and significant customer satisfaction. This research is expected to be an input for Maybelline company policy-making in marketing. Keywords: price, product quality, promotion, customer satisfaction, repurchase intention